Faʿāliyyah Istikhdām al-Ṭarīqah al-Mubāsharah bi Luʿbah Lughawiyyah Wassimniy li Tarqiyah Itqān al-Mufradāt - Hendri, Muspika; Bardansyah, Yasmaruddin; Rambe, Pangadilan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aimed at finding out the effectiveness of using Direct method with “Label Me” language game in increasing student Arabic vocabulary mastery at the eighth grade of Islamic Junior High School of Muhammadiyah 02 Pekanbaru. It was quasi-experiment research. All the eighth-grade students at Islamic Junior High School of Muhammadiyah 02 Pekanbaru were the population of this research, and they were 213 students. The samples were 36 the eighth-grade students of class A and 36 students of class B, and they were 72 students. Test and observation were the instruments of collecting data. Based on the result of pretest and posttest in the experiment group, the score obtained was 6.6, and the control group was 5.5. Based on analyzing data by using t-test formula, the score of tobserved 4.83 was higher than ttable 2.381 at 1% significant level and 1.667 at 5% significant level. So, Null hypothesis (H0) was rejected and Alternative hypothesis (Ha) was accepted. It meant that there was a significant effect of Direct method with “Label Me” language game toward vocabulary mastery. In the observation table, the score of Direct method with “Label Me” language game was 96.7%, it was very good because it was in the significant level of 90%-100%. With these data, Direct method with “Label Me” language game was stated effective in increasing student vocabulary mastery at the eighth grade of Islamic Junior High School of Muhammadiyah 02 Pekanbaru. يهدف إلى معرفة فعالية استخدام الطريقة المباشرة بلعبة لغوية